Modification of Character Building in Online Learning - Musnar Indra Daulay; Nurhidayah Sari (STAI Hubbulwathan Duri, 2023)
Efforts to apply character values useful for students can be obtained from science with the help of an educator such as parents, teachers, and lecturers. This study aims to find out how character education during the covid-19 pandemic. This study used a qualitative descriptive method with 14 teachers as respondents who were interviewed directly by the researchers. The results showed that during the pandemic, the implementation of character education was reflected in the learning steps that had been outlined in the lesson plan. There is a modification in the implementation of character education during the pandemic. Teachers provide moral messages on the sidelines of online learning, sending proverbs, pictures, and short videos containing advice for students in accordance with attitudes that must be instilled according to the curriculum. This modification of the implementation of character education can be applied to online learning.